Brief Report: Macrophage Activation in HIV-Infected Adolescent Males Contributes to Differential Bone Loss by Sex. (1st August 2016) - Ruan, Alexandra; Tobin, Nicole H.; Mulligan, Kathleen; Rollie, Adrienne; Li, Fan; Sleasman, John; Aldrovandi, Grace M.
Abstract : Abstract: Accumulating evidence suggests that rates of low bone mass are greater in HIV-infected males than females. Of 11 biomarkers assessed by sex and HIV-status, HIV-infected males had increased levels of soluble CD14 which inversely correlated with bone mineral content and bone mineral density measures, suggesting macrophage activation as a possible mechanism of differential bone loss. Abstract : Supplemental Digital Content is Available in the Text.